The Declarable Future - Boyden, Jennifer (Book collections on Project MUSE., 2013)
In this collection of poems, a lost man wanders among the towns of people who can't remember what they named the children, how to find each other's porches, or whether their buildings are still intact. That's why they need the person with the loupe. Among the poems where doorknobs emit the daily news, stone angels fall from the sky, and the floating world's harvest is whatever swims too close, the person with the loupe steadfastly verifies only what can be measured, while the lost man is witness to the unquantifiable and the limitless.